Differential Loss of Presynaptic Dopaminergic Markers in Parkinsonian Monkeys - Diane T. Stephenson Ph.D.; Mary Abigail Childs; Qiu Li; Santos Carvajal-Gonzalez; Alan Opsahl; Mark Tengowski; Martin D. Meglasson; Kalpana Merchant; Marina E. Emborg (Cell Transplantation, 2007)
Assessment of dopamine nerve terminal function and integrity is a strategy employed to monitor deficits in Parkinson's disease (PD) patients and in preclinical models of PD. Dopamine replacement therapies effectively replenish the diminished supply of endogenous dopamine and provide symptomatic benefit to patients. Tyrosine hydroxylase (TH), dopamine transporter (DAT), vesicular monoamine transporter 2 (VMAT2), and amino acid decarboxylase (AADC) are widely used markers of dopaminergic neurons and terminals. The present studies were initiated to: (a) assess alterations in all four markers in the MPTP primate model of dopaminergic degeneration and (b) to determine whether L-DOPA treatment may itself modulate the expression of these markers. MPTP treatment induced a significant decline of dopaminergic immunoreactive fiber and terminal density in the basal ganglia. The amount of reduction varied between markers. The rank order of presynaptic marker loss, from most to least profound reduction, was TH > VMAT2 > DAT > AADC. Semiquantitative image analysis of relative dopaminergic presynaptic fiber and terminal density illustrated region-specific reduction of all four markers. Double immunofluorescence colocalization of two presynaptic markers on the same tissue section confirmed there was a more dramatic loss of TH than of VMAT2 or of DAT following MPTP treatment. L-DOPA treatment was associated with a significantly higher level of AADC and VMAT2 immunoreactivity in the caudate nucleus compared to placebo. These results illustrate that neurotoxic injury of the dopamine system in primates leads to altered and differential expression of presynaptic dopaminergic markers in the basal ganglia and that expression of such markers may be modulated by L-DOPA therapy. These findings have implications for the use of biomarkers of disease progression as well as for the assessment of neurorestorative strategies, such as cell replacement, for the treatment of PD.